Bodies of maize, eaters of grain : comparing material worlds, metaphor and the agency of art in the Preclassic Maya and Mycenaean early civilisations - Bajema, Marcus Jan (Archaeopress Publishing Ltd, 2017)
'Bodies of Maize, Eaters of Grain' provides a comparative study of the earliest urban civilisations of the Maya lowlands and the Greek mainland. It builds upon earlier comparative studies by Gordon Childe, Robert Adams and Bruce Trigger, extending their work into new directions. Specifically, the focus lies on the art styles of the Late Preclassic lowland Maya and Mycenaean Greece. The approach used here seeks to combine more traditional iconographic approaches with more recent models on metaphor and the social agency of things